2019
DOI: 10.1371/journal.pone.0226551
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gut passage by waterbirds on the seed coat and pericarp of diaspores lacking “external flesh”: Evidence for widespread adaptation to endozoochory in angiosperms

Abstract: The widely accepted “endozoochory syndrome” is assigned to angiosperm diaspores with a fleshy, attractive tissue and implies the existence of adaptations for protection against digestion during gut passage. This syndrome has led diaspore fleshiness to be emphasized as the exclusive indicator of endozoochory in much of the ecology and biogeography research. Crucially, however, endozoochory in nature is not limited to frugivory, and diaspores without “external flesh” are commonly dispersed, often over long dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 82 publications
(105 reference statements)
2
48
0
Order By: Relevance
“…Data for (d) and (e) were from the LEDA traitbase (Kleyer et al., 2008), data for (g) and (h) from the Baseflor database (Julve, 1998). Dispersal syndromes are not reliable indicators of dispersal mechanisms since they only assign endozoochory for fleshy‐fruited plants (Costea et al., 2019). However, since they assign the plant species studied to water, wind and other vectors, birds feeding in different ways may be expected to ingest seeds from different syndromes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data for (d) and (e) were from the LEDA traitbase (Kleyer et al., 2008), data for (g) and (h) from the Baseflor database (Julve, 1998). Dispersal syndromes are not reliable indicators of dispersal mechanisms since they only assign endozoochory for fleshy‐fruited plants (Costea et al., 2019). However, since they assign the plant species studied to water, wind and other vectors, birds feeding in different ways may be expected to ingest seeds from different syndromes.…”
Section: Methodsmentioning
confidence: 99%
“…Most angiosperms have dry indehiscent fruits or small seeds released from dehiscent fruits (Julve, 1998). Many plant taxa are dispersed by vertebrate vectors such as ungulates or waterbirds, in which plants obtain benefits from seeds that survive gut passage and are effectively dispersed, and animals obtain food from foliage and from the fraction of seeds digested during gut passage (Albert et al., 2015; Costea et al., 2019). Migratory waterbirds are particularly important for long‐distance dispersal, and hence for maintaining ecosystem biodiversity and functioning, genetic flow or mixing between plant populations (Kleyheeg, Treep, de Jager, Nolet, & Soons, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Seeds were dehydrated through an ethanol series (50%, 70%, 85%, 95%, and 100%; each step 1h) and then dried with a Tousimis Autosamdri-931 critical point dryer. Using SEM has been proven to be a valid approach to study not only the external morphology of seeds, but also the seed coat anatomy in Cuscuta [13,14]. For anatomy, 5-10 seeds were sectioned longitudinally by hand with a razor blade along the hilum area.…”
Section: Seed Morphology and Anatomymentioning
confidence: 99%
“…In Cuscuta, the inner (or single palisade when only one palisade layer is present outside hilum area) is strongly lignified and it represents the ultimate mechanical defense of the seeds. Bird endozoochory experiments reported that gut passage partially or entirely stripped the outer palisade layer, while the inner or single palisade layer was little affected [13,14]. If the function of the inner palisade layer (or single one in Monogynella) is to safeguard the impermeability of the seed coat, ensure physical dormancy and provide an ultimate line of mechanical defense, the role of the external palisade layer is not clear.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation